Quality and safety assessment of goat milk collected from different regions of Mathura city - Ojha, Sadhana; Pathak, Vikas; Goswami, Meena; Bharti, Sanjay Kumar; Singh, Tanuja (Indian Journal of Dairy Science, 2020)
The present study was carried out for quality and safety assessment of goat milk from five different regions of Mathura city viz. Holigate, Sadar, Aurangabad, Chungi and Township. The milk samples were collected from dairy shops, vendors and milk producers and evaluated on the basis of various organoleptic tests, physico-chemical properties, proximate estimation and microbiological studies following the standard procedures. Among organolpetic tests, Chungi (70%) and Township (90%) samples had clearer appearance than the other area. All sample collected from township is white in color. Regarding texture/consistency of milk, the sample procured from T having normal consistency and normal odor.Â  The COB test was positive in 20 and 10% samples of H and S areas only. There was no significant difference in temperature, pH and titrable acidity of milk of different areas. However, the specific gravity showed significant (P